Salivary pepsin detection for laryngopharyngeal reflux diagnosis: sensitivity and specificity comparison with scoring system: Salivary pepsin detection for LPR diagnosis - Kandhi, Putu Wijaya; Manurung, Rosauli; Wicaksono, Pandu (PERHATI-KL, 2025)
Background: Laryngopharyngeal reflux (LPR) is characterized by the backflow of stomach contents into the larynx and pharynx. Gastroesophageal reflux disease (GERD) is a similar condition often mistaken for LPR. Detection of oral salivary pepsin has been developed as an alternative diagnostic modality for LPR. Additionally, there are diagnostic aids for LPR utilizing scoring systems, namely Reflux Symptoms Score (RSS) and Reflux Sign Assessment (RSA). Purpose: To assess the sensitivity and specificity of saliva pepsin testing compared to RSS and RSA in diagnosing LPR. Method: A prospective cross-sectional study involving 30 subjects with LPR symptoms was conducted to evaluate the diagnostic accuracy of saliva pepsin levels compared to RSS and RSA scores in LPR patients. Diagnostic tests performed included sensitivity, specificity, Positive Predictive Value (PPV), and Negative Predictive Value (NPV). Result: The male-to-female ratio was 1:1.3. Saliva pepsin testing with a cutoff value of ≥16 ng/mL, demonstrated a sensitivity of 100%, specificity of 90%, PPV of 95.24%, and NPV of 100% against the RSS questionnaire. Meanwhile, when assessed against the RSA questionnaire, saliva pepsin testing showed a sensitivity of 95.24%, specificity of 88.89%, PPV of 95.24%, and NPV of 88.89%. The results indicated that saliva pepsin testing had good sensitivity and specificity, with values of 100% and 90%, respectively, against the RSS questionnaire; and 95.24% and 88.98%, respectively, against the RSA questionnaire. Conculsion: Saliva pepsin testing could be used as a primary diagnostic modality in the future due to its non-invasive nature, ease of administration, and good patient tolerance.